POLITICAL SHAMANS IN A FOUCAULDIAN PERSPECTIVE: HOW SHAMANS REMAIN PRESENT IN POLITICAL CONTESTATION - Anggi Fransiska Putri (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This article is not explaining how scientifically shamans are able to smooth the way for candidates in winning electoral politics, but rather this article aims to explain how the formation of discourse is built to support the rationality of political shamans so that there are still many who trust and use their services. Using the object of study at the moment of the election of the village head (pilkades) in Pangro Village in Central Java, the Foucauldian analysis attempts to examine the foundation of knowledge why shamans can have the role of